Islamic Classroom Management Model in Thailand’s Primary Schools - Zahra Khusnul Lathifah; R. Siti Pupu Fauziah; Radif Khotamir Rusli (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to reveal the islamic classroom management model in Thai Elementary Schools. This study was a case study to find deeper and comprehend a phenomenon of managing classrooms in Thailand’s lower primary school, Saengshatta. This study data were from observing four classes (year 1 to year 4) in the school, interviews with teachers and principals, and documenting the physical aspect of management. The data were gathered based on Kellough and Kellough’s practical classroom principles. The data were analyzed using Kellough’s theory by selecting the data into three categories; the plan, the setup, the evaluation, and transforming it into a conclusion. This study revealed that the Saengshatta school applied Islamic values to organizing and conducting the classroom. The organizing is shown by the lay-outing of the class based on the shape of the class; the group made, the individual weekly checking up of the students, the rules and obligations created to manage the time for the teachers and the students, and the learning media were contextualized into Islamic values. Islamic values are integrated into many approaches such as power, threat, freedom, recipe, teaching, group process, and pluralism. The model that Saengshatta applied were humanistic, democratic, and behavioristic.